Globalization, environmental change, and social history - Boomgaard, P., 1946-2017; Hart, Marjolein 't, 1955- (International review of social history. Special issue, 2010)
Social and environmental historians assess the extent to which transnational agents changed socioecological space as a consequence of globalization.